Role of crustal fluid in triggering moderate to major earthquakes: evidence from aftershock data of two recent large tremors (Journal of Nepal Geological Society, 2008)
A number of models have been proposed for the role of fluids and high pore pressures in the mechanics of fault slip and the nucleation of earthquakes, e.g., dilatancy-diffusion, mineral dehydration, frictional heating, fluid pressure-activated fault valves and hydrofracturing, partially sealed fault zones, a spatially varying stress tensor without hydrofracturing, and fluid involved weak and strong patch failures. In this study, the availability of fluid in the upper and lower crust was analysed carefully, as the fluid may be responsible for triggering large earthquakes. The anomalies observed in the three-dimensional tomographic images from the source regions of the 2001 Gujarat and 1995 Kobe earthquakes, obtained after inversion of aftershock data, can be attributed to the presence of the fluid. A tomographic inversion was also applied to the aftershock data from the 26 January 2001 Bhuj earthquake (Mw 7.7) in the state of Gujarat in western India. We used arrival times from 8,374 P and 7,994 S waves of 1,404 aftershocks recorded on 25 temporary seismic stations. It seems that the aftershock distribution corresponds to the high-velocity anomalies. Low P- to S-wave velocity ratio (Vp/Vs) anomalies are generally found at depths of 10 to 35 km, i.e. the depth range of the aftershock distribution. However, relatively high Vp/Vs and low Vs characterise the deeper region below the hypocentre of the mainshock, at depths of 35 to 45km.This anomaly may be due to a weak fractured and fluid-filled rock matrix, which might have contributed to triggering this earthquake. This anomaly exists in the depth range of 35 to 45 km, and extends 10 to 12 km laterally. This earthquake occurred on a relatively deep and steeply dipping reverse fault with a large stress drop.Similarly, the 17 January 1995 Kobe earthquake (M 7.2) in southwest Japan had a strike-slip focal mechanism and it caused a rupture at a 17 km depth. The Kobe main shock hypocentre is located in a distinctive zone characterised by low P- and S-wave velocities and a high Poisson's ratio. This anomaly exists in a depth range of 16to 21 km, and extends 15to 20km laterally. This anomaly can be attributed to a fluid-filled, fractured rock matrix that contributed to the initiation of the Kobe earthquake. The existence of fluids in and below the seismogenic layer may affect the long-term structural and compositional evolution of the fault zone, change the fault zone strength, and alter the local stress regime. These influences can be exerted through the physical role of fluid pressure and a variety of chemical effects, such as stress corrosion and pressure solution. These influences would have enhanced stress concentration in the seismogenic layer leading to mechanical failure of a strong asperity, and thus may have contributed to the nucleation of the Kobe earthquake.The area of low Vs and high Vp/Vs values can be seen in a depth range of35 to45km beneath the main shock hypocentre. These features are very similar to the velocity anomaly also observed, in a depth range of 16 to 21 km, in the hypocentre region of the1995 Kobe earthquake. Such an anomaly possibly indicates the existence of a fluid-filled, fractured rock matrix, which may have contributed to the initiation of large earthquakes. The fluid in a depth range of35to45km might have also triggered the 200I Gujarat earthquake.